Optical Coherence Tomography Findings in the Retinas of SOD1 Knockout Mice - Augustin, Marco (Transl Vis Sci Technol, 2020)
PURPOSE: The retinal phenotype of popular mouse models mimicking ophthalmic diseases, such as the superoxide dismutase 1 (SOD1) knockout (KO) mouse model, has mainly been assessed by ex vivo histology and in vivo fundus photography. We used multifunctional optical coherence tomography (OCT) to characterize the retinas of SOD1 KO mice in vivo. METHODS: The custom-made ophthalmoscope featured a combination of conventional OCT, polarization-sensitive OCT, and OCT angiography. Seven SOD1 KO mice and nine age-matched controls were imaged between 6 and 17 months of age. A postprocessing framework was used to analyze total and outer retinal thickness changes. Drusenlike lesions were segmented, and their sizes and the number of lesions were assessed quantitatively. Their appearance in the conventional reflectivity images, as well as in the corresponding polarization-sensitive images, was characterized qualitatively. RESULTS: Drusenlike lesions increased in size and number with age for SOD1 KO mice. Exploiting the multiple contrast channels, the appearance of the lesions was found to resemble pseudodrusen observed in eyes of patients suffering from dry age-related macular degeneration. The total and outer retinal thicknesses were lower on average after 11 months and 7 months in SOD1 KO mice compared with age-matched controls. Neovascularizations were found in one out of seven KO animals. CONCLUSIONS: OCT imaging proved beneficial for a detailed in vivo characterization of the pathological changes in SOD1 KO mice. TRANSLATIONAL RELEVANCE: Phenotyping of animal models using modern imaging concepts can be conducted with more precision and might also ease the translation of conclusions between clinical and preclinical research.